Frequency and risk factors of retinopathy of prematurity: a 5-year single-center study in a Tertiary Care Hospital - Maaly Abdel Fattah; Anas AlKhabaz; Ibrahim Issa; Hadeel Alhemsi; Kassem AlSaad; Eyad AlMidani; Faisal Khan (Journal of the Egyptian Ophthalmological Society)
Aim Our study aimed to determine the frequency of retinopathy of prematurity (ROP) in a cohort of premature infants screened for ROP, to confirm the efficacy of our screening program used in the NICU to avoid childhood blindness. In addition, we aimed to study the associated risk factors affecting ocular status including birth weight (BW), gestational age (GA), mechanical ventilation, length of intensive care unit (ICU) stay, and number of ROP follow-up. Methods This was a retrospective cohort study conducted from March 2016 to March 2021. Data were retrieved from the records of preterm infants admitted to the neonatal intensive care unit in King Faisal Specialist Hospital and Research Center in Riyadh, Saudi Arabia. The included data: Comprised perinatal data such as sex, BW, GA, multifetal gestation, and delivery type. Neonatal course: Need for surfactant, oxygen therapy, and mechanical ventilation (MV) duration. Neonatal complications: Chronic lung diseases [(respiratory distress syndrome (RDS) and bronchopulmonary dysplasia (BPD)], sepsis, neonatal jaundice, patent ductus arteriosus (PDA), hydrocephalus, and intraventricular hemorrhage (IVH). ROP examination: stage, zone, plus disease, extent, treatment, and number of the follow-up. Results In all, 337 preterm infants met the screening criteria and were included in the study. The majority (52%, n=177) were male; 148 (43.9%) were products of multifetal gestation, the mean GA was 29.35±2.77, and the median BW was 1195.1±338 gm. Caesarean section was the main mode of delivery in 80.5% of our sample (269 babies). ROP was detected in 181 (53.7%) infants, of which 110 (32.6%) had Stage 1, 57 (17%) Stage 2, and 14 (4.15%) had Stage 3. The majority (89.4%) were involved in zone 2–3, and five patients had the plus disease (1.48%). The number of ROP follow-up ranged between 2 and 25 visits either in the NICU or in the eye clinic following their discharge with a mean of 2.347. Conclusion The incidence of ROP in our sample was high relative to other local studies, which was related to the relatively high number of multifetal gestations with high chance of low birth weight as our center is an expert facility in in vitro fertilization. Male patient had a high incidence of development of different stages of ROP. Preterm babies with complicated neonatal course like NEC, Chronic Lung Disease, and IVH had high incidence of development of ROP.